Effects of recreation on soil properties in Kanching Recreation Forest, Malaysia - Jusoff, Kamaruzaman (1989)
The recreation forest area in the Kanching Forest Reserve subjected to ten years of intensive recreational use is beginning to show signs of soil deterioration. A study to determine the effects of past recreation on the forest soil environment clearly showed surface compaction and some sheet erosion. Surface soil moisture on the areas compacted by recreation activities was depleted and will be critical for the growth of ground cover. Initial changes involve the loss of surface leaf litter, reduction of organic horizon thickness followed by formation of the thin, compacted upper mineral horizon. This information can be used to assist managers in selecting recreational sites and ensuring appropriate site management practices.